2020
DOI: 10.1177/1557988320901377
|View full text |Cite
|
Sign up to set email alerts
|

Use of Digital Health Information for Health Information Seeking Among Men Living With Chronic Disease: Data From the Health Information National Trends Survey

Abstract: Although diabetes education plays an important role in self-management for people living with diabetes, male health “help-seeking” lags far behind women. These gender-related “help-seeking” disparities often result in males being less engaged in their health care, which subsequently leads to poorer health outcomes among males. In this cross-sectional study, we used data from the 2017 Health Information National Trends Survey (HINTS) to identify factors that may contribute to communication inequalities between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 39 publications
4
28
0
3
Order By: Relevance
“…Females had a significantly higher probability of using ePHI online management compared to males [ 22 , 23 ], but there is no significant difference in online patient-provider communication [ 5 , 23 ]. Income level was reported to be positively associated with eHealth sum score, a composite score representative of using technology to access health care [ 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Females had a significantly higher probability of using ePHI online management compared to males [ 22 , 23 ], but there is no significant difference in online patient-provider communication [ 5 , 23 ]. Income level was reported to be positively associated with eHealth sum score, a composite score representative of using technology to access health care [ 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the evidence documenting the effectiveness of internet-based interventions in improving chronic disease outcomes and the wealth of health information available, access and uptake of health information remains a challenge, thus potentially increasing health disparities across race/ethnicity, socioeconomic status, and language [ 12 , 13 , 14 , 15 , 16 ]. In particular, studies have observed gaps in internet use for specific health outcomes (e.g., cancer, cardiovascular disease) across race/ethnicity, age, and gender [ 17 , 18 , 19 , 20 , 21 , 22 ]. A secondary analysis of data from the Pew Research Center observed that racial and ethnic minority groups were more likely to contribute to COVID-19 content on social media [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Um estudo americano realizado com 1.254 homens mostrou que a população masculina está mais hesitante em procurar serviços de saúde numa base preventiva, o que no futuro resultará em problemas de saúde nestes indivíduos. O estudo revelou ainda que a maioria dos indivíduos eram hipertensos, diabéticos, obesos e tinham problemas cardíacos (Sherman, Patterson, Tomar, & Wigfall, 2020). Outro dado importante apontado na presente investigação está relacionado com a elevada taxa de pacientes com DM e/ou HAS como comorbilidade antes do internamento.…”
Section: Discussionunclassified
“…Foi também identificada uma associação significativa entre os doentes colonizados com GMR e o NAS médio, o NAS no primeiro dia e o NAS do último dia de internamento, respectivamente (56,8 p < 0,000; 73,1 p < 0,000; e 66,2 p < 0,02). Num estudo retrospetivo realizado em nove unidades de cardiologia intensivas, a partir de um hospital público, de elevada complexidade, com uma amostra de 835 doentes (Sherman et al, 2020), observou-se que a carga de trabalho medida pelo NAS não influenciou a ocorrência de infeções relacionadas com cuidados de saúde nas unidades de cardiologia intensivas investigadas.…”
Section: Discussionunclassified